Intercultural learning in language education and beyond : evolving concepts, perspectives and practices - McConachy, Troy, 1980-; Golubeva, Irina; Wagner, Manuela (Educator) (Languages for intercultural communication and education ; 38, 2022)
"This book provides a contemporary and critical examination of the theoretical and pedagogical impact of Michael Byram's pioneering work on intercultural communicative competence and intercultural citizenship. The book offers comprehensive, up-to-date and accessible knowledge for researchers, teachers, teacher-trainers and students"--